Compact laser probe for surface acoustic waves - Semenov, V.V.; Blonskyi, I.V.; Gryts, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Our compact laser probe for surface acoustic waves (SAW) is designed to
study properties of SAW substrates and control technological processes of their
manufacturing. These substrates are widely used in device manufacturing, controlling
systems, consumer electronics, etc. In this probe, we use the Bragg modulator in the
double-pass scheme, which provides its compactness and multifunctionality.